Cataract surgery coverage rates for Indigenous and non‐Indigenous Australians: the National Eye Health Survey. Issue 6 (18th September 2017) - Foreman, Joshua; Xie, Jing; Keel, Stuart; van Wijngaarden, Peter; Crowston, Jonathan; Taylor, Hugh R; Dirani, Mohamed
Abstract: Objective: To determine cataract surgery coverage rates for Indigenous and non‐Indigenous Australians. Design: National cross‐sectional population‐based survey. Setting: Thirty randomly selected Australian geographic sites, stratified by remoteness. Participants: 3098 non‐Indigenous Australians aged 50 years or more and 1738 Indigenous Australians aged 40 years or more, recruited and examined in the National Eye Health Survey (NEHS) between March 2015 and April 2016. Methods: Participants underwent an interviewer‐administered questionnaire that collected socio‐demographic information and past ocular care history, including cataract surgery. For those with visual acuity worse than 6/12, anterior segment photography and slit lamp examinations were conducted. Main outcome measures: Cataract surgery coverage rates according to WHO and NEHS definitions; associated risk factors. Results: Cataract surgery coverage rates calculated with the NEHS definition 1 of vision impairment (visual acuity worse than 6/12) were lower for Indigenous than non‐Indigenous participants (58.5% v 88.0%; odds ratio [OR], 0.32; P < 0.001). According to the World Health Organization definition (eligibility criterion: best‐corrected visual acuity worse than 6/18), coverage rates were 92.5% and 98.9% for Indigenous and non‐Indigenous Australians respectively. Greater age was significantly associated with higher cataract surgery coverage in Indigenous (OR, 1.41 per 10 years; P = 0.048) and non‐Indigenous Australians (OR, 1.58 per 10 years; P = 0.004). Conclusions: The cataract surgery coverage rate was higher for non‐Indigenous than Indigenous Australians, indicating the need to improve cataract surgery services for Indigenous Australians. The WHO definition of the coverage rate may overestimate the cataract surgery coverage rate in developed nations and should be applied with caution.